The Non-Observance of the Conversational Maxims: An Analysis of the Dialogues in Arthur Miller’s the Crucible - Yuvike, Yuvike; Winiharti, Menik (Lingua Cultura, 2009)
Article deploys the application of Cooperative Principle in analyzing the dialogues in Arthur Miller’s The Crucible.The applied research methods were qualitative and quantitative methods. The dialogue of the play were transferred in the form of excerpts to the computer manually. Then the pplication of The Non-observance of the Conversational Maxims was analyzed and its occurences are counted. It is found that The Non-observance of the Conversational Maxims are applied in the play. The categories of The Non-observance of the Conversational Maxims that are applied are flouting the maxims, violating the maxims, and opting out a maxim. The most frequent category of The Non-observance of the Conversational Maxims is flouting quality by using metaphor while the least frequent one is flouting quantity.